ARE THE HABITUAL PRACTICE OF PHYSICAL ACTIVITY, DIETARY HABITS, ANTHROPOMETRIC INDICATORS, AND AUTONOMIC MODULATION ASSOCIATED WITH THE PREVALENCE OF HIGH BLOOD PRESSURE? - Lombardi, Gisele; Fernandes, Rômulo Araújo; Christofaro, Diego Destro; Casonatto, Juliano (Universidade Estadual de Maringá, 2016)
ABSTRACT Objective: To analyze the prevalence and association between high blood pressure, general and abdominal obesity, indicators of autonomic activity, habitual physical activity, and dietary habits in public schools in Londrina / PR. Methods: 189 subjects were evaluated (75 males and 114 females), 10-17 years. Assessment of habitual physical activity and dietary habits was performed. Anthropometric measurements were performed, in addition to measurement of resting blood pressure and heart rate variability. The chi-square test was used to assess associations between blood pressure (dependent variable) and other variables. Those that were significantly associated were submitted to Poisson regression to identify the magnitude of the association. Results: Individuals with abdominal obesity were 2.3 times more likely (P = 0.002) to present high blood pressure. Conclusion: Individuals with abdominal obesity are approximately twice as likely to have high blood pressure, independent of obesity levels, which in turn, are not associated with increased blood pressure.

RESUMO Objetivo: Analisar a associação entre pressão arterial elevada, obesidade geral e abdominal, indicadores de atuação autonômica, prática habitual de atividade física e hábitos alimentares na rede pública de ensino de Londrina/PR. Métodos: Foram avaliados 189 sujeitos (75 masculino e 114 feminino), com idade entre 10 e 17 anos. Foram realizadas avaliações antropométricas, além da pressão arterial de repouso, atuação autonômica, hábitos alimentares e prática habitual de atividade física. O teste qui-quadrado foi aplicado para verificar associações da pressão arterial (variável dependente) com as demais variáveis. Aplicou-se também a regressão de Poisson para identificação da magnitude da associação. Resultados: Obesidade e obesidade abdominal foram associadas à pressão arterial elevada. Indivíduos com obesidade abdominal obtiveram 2,3 vezes mais chance (P=0,002) de apresentarem pressão arterial elevada. Conclusão: Adolescentes com obesidade abdominal possuem aproximadamente duas vezes mais chances de apresentarem pressão arterial elevada, independente dos níveis de obesidade.
PRÁTICA HABITUAL DE ATIVIDADE FÍSICA, HÁBITOS ALIMENTARES, MODULAÇÃO AUTONÔMICA E INDICADORES ANTROPOMÉTRICOS ESTÃO ASSOCIADOS À PREVALÊNCIA DE PRESSÃO ARTERIAL ELEVADA?
Keywords: Nutritional status; Autonomic nervous system; Motor activity; Estado nutricional; Sistema nervoso autônomo; Atividade motora